Management control systems and the use of digital platforms: a multi case study comparison. (2016) - Mancini, Daniela; Corsi, Katia
This study investigates the contribution of digital platforms (DPs) to management control systems (MCSs). DPs, generally, provide tools useful to create, organise, search, and share documents, information, ideas, calendars, and so on. Prior studies provided little attention to these platforms and how they can become a tool to support management control processes. In this work, we aim to analyse how DPs affect each components of the MCSs in different organisational contexts using a multi case study comparison. Our findings highlight the impacts of DPs on MCSs and the contribution of DPs to increase the level of integration among MCS components. Moreover, we identify some contingency factors, which influence how DPs affect MCSs. The paper contributes both to theory, filling the gap in studies regarding the relationship between MCSs and information and communication technologies (ICTs), and to practice, showing how a DP could be designed, implemented, and used to improve MCSs.